2021
DOI: 10.1186/s12939-021-01549-5
|View full text |Cite
|
Sign up to set email alerts
|

‘It was hell in the community’: a qualitative study of maternal and child health care during health care worker strikes in Kenya

Abstract: Background Health care workers in Kenya have launched major strikes in the public health sector in the past decade but the impact of strikes on health systems is under-explored. We conducted a qualitative study to investigate maternal and child health care and services during nationwide strikes by health care workers in 2017 from the perspective of pregnant women, community health volunteers (CHVs), and health facility managers. Methods We conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…This case study found evidence of system-level interactions between CHAG and the GoG to maintain service continuity during strikes which allowed for mostly ‘absorptive’ resilience strategies, including public announcements encouraging patients to seek care in CMIs. In contrast to studies exploring health system resilience during strikes in Kenya ( Waithaka et al ., 2020 ; Scanlon et al ., 2021a ; 2021b ; Adam et al ., 2018 ), these interactions were not ad-hoc, taken on by individual frontline managers and inconsistent but occurred on a national level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This case study found evidence of system-level interactions between CHAG and the GoG to maintain service continuity during strikes which allowed for mostly ‘absorptive’ resilience strategies, including public announcements encouraging patients to seek care in CMIs. In contrast to studies exploring health system resilience during strikes in Kenya ( Waithaka et al ., 2020 ; Scanlon et al ., 2021a ; 2021b ; Adam et al ., 2018 ), these interactions were not ad-hoc, taken on by individual frontline managers and inconsistent but occurred on a national level.…”
Section: Discussionmentioning
confidence: 99%
“…Strike action is experienced globally but the effects are particularly severe in LMICs due to pre-existing health system fragilities ( Russo et al ., 2019 ; Waithaka et al ., 2020 ). Though there is conflicting evidence on the direct effects of HWS on population mortality ( Cunningham et al ., 2008 ; Metcalfe et al ., 2015 ), strikes in LMICs are thought to have significant health systems effects, for example leading to a decrease in in/out-patient flow, a breakdown in trust between community and health workers, decreasing health worker motivation or entrenching inequalities as strike effects are felt disproportionately by the poor ( Waithaka et al ., 2020 ; Scanlon et al ., 2021a ; 2021b ; Adam et al ., 2018 ). HWS are concerning as human resources for health (HRH) are arguably the most fundamental building block of a health system ( World Health Organization, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that in 2017, the public health system was near collapse due to the health workers’ strike in Kenya. 54 This reduced hospital admissions and outpatient services, including skilled delivery. 55 Poor women are most affected by health workers’ strikes since they are least likely to afford care in private health facilities.…”
Section: Discussionmentioning
confidence: 99%
“… 55 Poor women are most affected by health workers’ strikes since they are least likely to afford care in private health facilities. 54 Despite the damaging effects of health workers’ strikes on maternal outcomes, they have become far too familiar in Nigeria since 2014. Resident doctors were on strike in Nigeria in 2021 when we drafted this manuscript, indicating that this has become a pervasive problem with dire implications for women and girls’ well-being.…”
Section: Discussionmentioning
confidence: 99%